Case Report: Capitalizing on Development and Activity-Dependent Plasticity, an Interaction With Pediatric-Onset Spinal Cord Injury - MacKenzie Goode-Roberts; Kathryn Noonan; Danielle Stout; Margaret Calvery; Margaret Calvery; Kyle Brothers; Nicole Williams Doonan; Andrea L. Behrman (Frontiers Media S.A., 2022)
BackgroundSpinal cord injury (SCI) in infancy halts typical development secondary to paralysis/paresis and the limited ability to engage with the environment. Traditional therapies further restrict a child via bracing, equipment, and medications. In contrast, activity-based restorative therapies (ABRT) promote activation of the neuromuscular system below the level of injury and affords a more typical sensorimotor experience.Case DescriptionA premature male infant exhibiting hypotonia, poor head control, and extremity weakness was diagnosed at age 5 months with a remote incomplete upper cervical SCI based on magnetic resonance imaging (MRI), presumed to have occurred perinatally. From 4 to 15 months of age, he received physical, occupational and speech therapies. Enrolled in an ABRT program at 15 months, he was unable to sit, pull-to-stand, stand, or walk and had upper extremity impairments. Results of the Bayley-III Scales of Infant and Toddler Development revealed gross and fine motor scores consistent with a 4-month-old.MethodsActivity-based restorative therapies was provided 5 day/week: 1.5 h of activity-based locomotor training and 1 h of activity-based occupational therapy.ResultsActivity-based restorative therapies are reported for 177 sessions and are on-going. Improvements are noted in trunk control, standing, walking, grasp, in-hand manipulation, and associated kinematics. Bayley-III fine motor score improved to that of a 16-month-old and gross motor score to that of a 7-month-old.DiscussionWhile the two treatment periods (i.e., 4-15 months old and 15-24 months) were each ∼9 months, the child's accelerated progress toward typical development during the latter, ABRT period is noteworthy. In comparison to the period of traditional therapies in which paralysis was compounded by a restrictive environment and compensation, ABRT provided a potentially rich sensorimotor experience with an emphasis on active weight-bearing and proper kinematics to activate the neuromuscular system below the lesion in an age-appropriate, task-specific context of activities. Improved physical capacity enabled exploration more typically associated with development at this age expanding the positive impact to other developmental domains.